Modification of Carbon Paste Electrode Using Oxovanadium(IV)acetylacetone Complex For Voltammetric Determination of Glucose - Mardhiyah, Hanifah
Glucose is one of monosaccharides with molecural formula C6H1206, which is very important in the metabolic process, energy sources, and increasing our brain's work. Glucose level s in our body should be in the standard level because if it is too low or too high , it can cause health problems. Glucose levels determination had been frequently researched, and the technique that can be used is electrochemical. The working electrode used in the technique was modified by enzime, main group metals, and complex of transition metals. In this research, carbon paste electrode modified by oxovanadium(IV)acetylacetone complex had heen used to determine glucose level hy voltammetry. The modification technique used in this research is complex solution addition on electrode's surface (insertion). Glucose standard solution determination was used by differential pulse voltammetry technique in the phosphate buffer solution pH of 7. Carbon paste electrode modified by oxovanadium(IV)acetylacetone had a good repeatability. However, the electrode had linear region in the glucose consentration range of0.4-l 11M; 1-10 11M: 20-90 11M; and 200-1000 11M with detection limit of 0.057 f1M. The electrode was used for glucose levels determination Yuzu drink sample. The result shows glucose recovery percentage of 1 02.14±0.821%